Ventura County Star Free Press Annual Retail Display Adversting Contract (1976)
This document is a May 28, 1976 annual retail display advertising contract between the Ventura County Star-Free Press and the Tolmach for Assembly Committee. The committee agrees to purchase at least 200 column inches of display advertising over a twelve-month period at a discounted rate of $3.42 per column inch, under the newspaper's annual bulk space pricing schedule. The contract outlines advertising rates, color charges, payment terms, interest on overdue accounts, rate adjustments based on actual space used, termination conditions, and the publisher's rights regarding copy approval, errors, and special editions. Overall, it formalizes a prepaid political advertising arrangement for a 1976 Assembly campaign.